An analysis on the spatial heterogeneity characteristics of landscape ecological risk in Qilian Mountain National Park - Li, Yanlong; Qin, Qianqian; Wang, Duowen; An, Wanxiu; He, Xiaohui; Yu, Tianquan (Frontiers in Forests and Global Change, 2024)
As a key ecological function area and a priority area for biodiversity conservation in China, Qilian Mountain National Park is facing a severe test of its ecological environment, and the study of its landscape ecological risk is of great significance to the construction and high-quality development of the Qilian Mountain National Park. In this research, based on land use data from six periods (i.e., year in 1995, 2000, 2005, 2010, 2015, and 2020) in the Qilian Mountain National Park, we divided the ecological risk plots, calculated the landscape pattern, and constructed the landscape ecological risk index to deeply explore the temporal and spatial heterogeneity of landscape ecological risk in Qilian Mountain National Park by using ArcGIS, Fragstats and GeoDa. The results showed that: Grassland is the predominant land use type, the area covered by woodland and grassland have exhibited a significant increase since 1995. Landscape fragmentation and disturbance indices exhibit fluctuations across different years, but showed an overall decreasing trend, and landscape stability was improved in the study area. There were obvious differences in the disturbance indices of different landscape types, with grassland and bare land having the highest values. Ecological risk in the study area is heterogeneous, with an overall low ecological risk and a shift to a lower risk level, and a decreasing trend in ecological risk, which is positively correlated spatially and mainly manifested as a “low-low” aggregation. Global warming and unreasonable human activities have exacerbated the ecological degradation of Qilian Mountain National Park, but a series of ecological restoration strategies after the establishment of the national park have gradually improved the regional ecological environment.